Playing With Power-Law Curves: A New Way to Analyze Market Structures and Sectors - Vogel, Harold L. (Archives of Business Research, 2022)
This paper outlines a universal empirical method that illustrates how such curves can be used to reveal changes in economic structures and relationships. The method takes power law analysis from a static snapshot to something more akin to a motion picture. The approach leads to an alternative to the classic Herfindahl-Hirschman sector concentration approach. It also provides a relatively stable characteristic numerical description for each sector and market segment and eliminates the biases caused by price inflation. Collection of such segment data can lead to a characteristic number, a signature, for a region’s economy or a company’s overall competitive position. The method is applicable in -- and can provide valuable new insights about -- an unlimited number of fields, for examples, everything from mergers and acquisition strategies and antitrust studies to sports, medical science, and entertainment.